Kobe Bryant - Christopher, Matt, 1917-1997; Stout, Glenn, 1958- (Matt Christopher legends in sports., 2021)
"This biography gives readers a courtside seat to the achievements of one of basketball's greatest legends as it traces Kobe's life from childhood to his five NBA championships to his successful career outside of the game to his tragic death and lasting legacy."--Provided by publisher.